Atomic Layer Deposited Zirconia Overcoats as On-Board Strontium Getters for Improved Solid Oxide Fuel Cell Nano-Composite Cathode Durability - Zhang, Yubo; Wen, Yeting; Huang, Kevin; Nicholas, Jason (Meeting abstracts (Electrochemical Society), 2020)
In order to improve the electrochemical performance of Solid Oxide Fuel Cells (SOFCs), nano-composite cathodes (NCCs), which are fabricated by adding nano-sized mixed ionic and electronic conducting (MIEC) catalysts into backbones of partially-sintered micro-sized ionic conducting particles via precursor solution infiltration, have been intensively studied. 1,2 Despite the reduced operating temperatures, poor long-term stability has still been observed for these high-performance NCCs. 3 As a low-temperature, nano-sized thin-film deposition method, atomic layer deposition (ALD) has been shown to help stabilize SOFC cathodes. 4 Therefore, in this work ZrO 2 overcoats of various thicknesses were deposited onto 12 vol% La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3-x (LSCF) - Gd 0.1 Ce 0.9 O 2 (GDC) NCCs using ALD. The initial 400 o C-700 o C electrochemical performance long-term 650 o C degradation behavior were studied with electrochemical impedance spectroscopy (EIS). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to investigate the microstructure of NCCs with different ZrO 2 thicknesses, while X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) were conducted to investigate aging-induced compositional changes. Figure 1 shows that no significant change in initial polarization resistance ( R P ) was observed for LSCF-GDC NCCs with 1-10 nm ZrO 2 ALD overcoats between 400 o C and 700 o C. However, as shown in Figure 2, while no significant ohmic resistance ( R 0 ) degradation happened for any of the LSCF-GDC NCCs, different R P aging behavior was observed for cells with different ZrO 2 thicknesses. Specifically, the 650 o C R P degradation rate dropped from ~45%/khrs for uncoated LSCF-GDC NCCs, to ~28%/khrs, ~18%/khrs, and ~12%/khrs for NCCs with 1, 2, and 5 nm of ZrO 2 overcoat, respectively, indicating improved durability. With 10 nm ZrO 2 overcoat, however, the R P degradation rate increased to ~87%/khrs. SEM analyses showed no evidence of LSCF particle coarsening for any of the cells, while XPS showed less inactive Sr species on the LSCF surface for ZrO 2 -coated cells after aging, compared with uncoated ones. As discussed in our recent paper on the subject, 5 this reduced inactive Sr species, together with the SrZrO 3 phase observed from detailed XRD analyses for ZrO 2 coated LSCF pellets after aging, suggested that the ZrO 2 overcoats act as Sr getters and react with inactive Sr species on the LSCF surface during aging. This reaction cleans up the LSCF surface and leads to better R P stability. For 10 nm overcoats, too much SrZrO 3 starts to accumulate on the LSCF surface during aging, causing the observed increase in the R P degradation rate. References T. E. Burye and J. D. Nicholas, J. Power Sources , 300 , 402–412 (2015). T. E. Burye and J. D. Nicholas, J. Power Sources , 276 , 54–61 (2014). M. Shah, P. W. Voorhees, and S. A. Barnett, Solid State Ionics , 187 , 64–67 (2011). Y. Gong et al., Nano Lett. , 13 , 4340–4345 (2013). Y. Zhang, Y. Wen, K. Huang and J. D. Nicholas, ACS Applied Energy Materials , 3 , 4057 (2020). Figure 1